THE EFFECT OF PERCEPTIONS OF USE, PERCEPTIONS OF EASE OF USE, AND SECURITY ON THE INTENTION OF MILLENNIAL CUSTOMERS TO USE BNI MOBILE BANKING THROUGH CUSTOMER TRUST AS INTERVENING VARIABLES - Septi Mariani Tis’a Ramadhani; Angga Putri Ekanova; Risa Amanda Putri (Asosiasi Dosen Muda Indonesia, 2022)
The rapid development of science and technology in the digital era, affects people's lifestyles when accessing a lot of information in various service functions through electronic means. Banks utilize information technology in mobile banking. The purpose of this study was to determine and analyze the effect of perceived benefits, perceived ease of use, and security on Millennial Generation customers' interest in using BNI Mobile Banking through customer trust as an intervening variable. The research method uses primary data obtained from distributing questionnaires to 100 millennial generations who have used BNI Mobile Banking in Jabodetabek. The analytical tools used are validity test, reliability test, R-square test, path coefficient test, indirect effect (path analysis), predictive relevance, and model suitability test. The results showed that perceived usefulness, perceived ease of use, and security had an effect on intention to use through customer trust in BNI Mobile Banking users. Perceived Usefulness, Perceived Ease of Use, and Security affect the Intention to Use BNI Mobile Banking Users. Perceived Usefulness, Perceived Ease of Use, and Security have direct and indirect effects on intention to use through Customer Trust in BNI Mobile Banking users.